2014
DOI: 10.1371/journal.pone.0111537
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378 Regulates Adiponectin Expression in Adipose Tissue: A New Plausible Mechanism

Abstract: AimsMechanisms regulating adiponectin expression have not been fully clarified. MicroRNAs (miRNAs), small non-coding RNAs that regulate gene expression, are involved in biological processes, including obesity and insulin resistance. We evaluated whether the miRNA-378 pathway is involved in regulating adiponectin expression.Methods and ResultsFirst, we determined a putative target site for miRNA-378 in the 3 prime untranslated region (3'UTR) of the adiponectin gene by in silico analysis. The levels of adiponect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 22 publications
(41 reference statements)
1
27
0
2
Order By: Relevance
“…Huang et al demonstrated that inhibition of MAPK1 by overexpressing mir-378a-5p in 3T3-L cells promotes adipogenesis and lipid accumulation [98]. Similar to this study, Ishida et al showed that the expression of miR-378a-5p is inversely correlated with the expression of adiponectin in obese rats, otherwise it positively correlates with the increase of TNF-α [104].…”
Section: Green Cluster: Adipogenic Process and Mirnassupporting
confidence: 79%
“…Huang et al demonstrated that inhibition of MAPK1 by overexpressing mir-378a-5p in 3T3-L cells promotes adipogenesis and lipid accumulation [98]. Similar to this study, Ishida et al showed that the expression of miR-378a-5p is inversely correlated with the expression of adiponectin in obese rats, otherwise it positively correlates with the increase of TNF-α [104].…”
Section: Green Cluster: Adipogenic Process and Mirnassupporting
confidence: 79%
“…Research in the field describes the regulation of miRNAs by adiponectin (11) or the regulation of adiponectin receptor expression by miRNAs (12,13). In murine cells, miR-21 and miR-378 have been reported to regulate adiponectin expression (14,15). Our results thus add an additional regulatory layer, namely the regulation of adiponectin itself by miRNA in human adipocytes.…”
Section: Discussionmentioning
confidence: 64%
“…miR-378 has been shown to regulate adiponectin level by binding to the 3′UTR of the adiponectin. Further, overexpression of miR-378 in 3T3L1 cells decreased mRNA and protein levels of adiponectin (Ishida et al 2014). A similar study in humans have shown significant association of serum adiponectin level with increased expression of miR-193b in white adipose tissue (Belarbi et al 2015).…”
Section: Introductionmentioning
confidence: 65%